Morphology as a Language for Aesthetics. From J.W. von Goethe to Olaf Breidbach - Quartesan, Ivan (Aesthetica Preprint, 2023)
The paper aims to understand whether morphology can be framed as a language for aesthetics. In particular, whether Olaf Breidbach’s contribution can determine its fundamental terms. These are related to the notion of forms and images. Hence, the paper is structured into three parts: i) framing of research on morphology in Germany; ii) analysis of Goethe’s method and vocabulary from an aesthetic standpoint; iii) presentation of Breidbach’s proposal in relation to Goethe.